Six-Year Immunologic Recovery and Virological Suppression of HIV Patients on LPV/r-Based Second-Line Antiretroviral Treatment: A Multi-Center Real-World Cohort Study in China - Huang, Xiaojie; Xu, Liumei; Sun, Lijun; Gao, Guiju; Cai, Weiping; Liu, Yanfen; Ding, Haibo; Wei, Hongxia; Ma, Ping; Wang, Min; Liu, Shuiqing; Chen, Yaokai; et al. (Frontiers in Pharmacology, 2019)
Objective This study was designed to evaluate the efficacy and safety of Lopinavir/ritonavir ( LPV/r )-based antiretroviral therapy ( ART) among HIV infected adults in China in whom the first-line therapy failed. Research design and method This was a large-scale, multi-center retrospective cohort study performed using treatment data from a national database covering HIV-infected adults receiving LPV/r-based second-line treatment from 2009 to 2016 across seventeen clinics in China. This study aims to evaluate the effectiveness and safety of LPV/r-based ART. The following were considered failures: patients with viral load at least 400 copies/ml at week 48, non-completers at week 48 for any reason and those who switched ART before week 48 for any reason such as side effects. Main outcome measures Treatment effectiveness was assessed by the rate of CD4+T cell recovery which was defined as >500 cells/mm3 and the proportion of patients achieving viral suppression, which was defined as <400 or <50 copies/ml due to different methods used during treatment. Safety was assessed by rates of LPV/r-related adverse events including lipid disorder, severe abnormal liver function, myelosuppression, and renal function. Results Between 2009 and 2016, 1196 participants (median 36 years, IQR 30–43 years) were finally enrolled. All had been on LPV/r -based second-line ART treatment for more than one year after any first-line ART regimen had failed. Overall CD4+T cell counts increased from 138 cells/mm3 to 475 cells/mm3 and 37.2% of all participants reached CD4 recovery. Viral suppression rates dramatically increased at the end of the first year (<400 copies/ml: 88.8%, <50 copies/ml: 76.7%) and gradually increased during follow-up (<400 copies/ml: 95.8%, <50 copies/ml: 94.4%). The most frequently reported AEs were LPV/r-induced lipid disorder and abnormal renal function. Conclusion This is the first real-world LPV/r-based second-line treatment study to cover such a large population in China. It provides clinical evidence that LPV/r-based second-line ART is effective in increasing CD4+T cell counts and viral suppression rates with tolerable side effects in HIV-infected adults in China in whom first-line treatment had failed.